Upaya guru untuk meningkatkan interaksi sosial siswa usia dini - Aciyaningsih Aciyaningsih; Itsnain Alfajri Husain (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
social interaction was an aspect of life that needs to be developed in early childhood. Armed with social interaction, early childhood is able to gain comfort in interacting. This study aims to determine how the teacher's efforts to improve social interaction in early childhood students. This research is a qualitative descriptive study. The data in this study were obtained from primary and secondary data. Primary data comes from three teachers and secondary data comes from references that are in accordance with this research study. Data were obtained through interview, observation, and documentation studies. The data were analyzed through discourse analysis using the Miles and Huberman model, namely reduction, display, and verification. The results showed that the efforts made by the teacher to increase social interaction were through preventive, curative, and promotive efforts. This research is expected to be the beginning of further research related to this research study.